Can soccer players return to sport after knee realignment osteotomy? - Daniel J. Chernoff; Thomas J. Kremen; Kristofer J. Jones (Elsevier, 2022)
Introduction: Knee realignment osteotomy can be the treatment of choice for unicompartmental arthrosis or symptomatic malalignment, but few studies report on return to sport rates among soccer players. Objectives: To review the available literature on return to sport rates for soccer players undergoing knee tibiofemoral realignment osteotomies. Methods: A literature review was performed and included a comprehensive search of the PubMed database using the following search items: "tibial osteotomy" AND "return to sport," "femoral osteotomy," AND "return to sport." Additionally, all articles' references were reviewed to identify any additional relevant studies. Results: A total of 31 studies report on knee realignment osteotomies and the rate for return to sport following these procedures. Overall, return to play rates are high, but there is significant variability amongst the literature regarding the types of sports and the physical demands that athletes are able to participate in after knee osteotomy. Conclusions: Soccer players can return to sport after knee realignment osteotomy, but at lower rates than other, lower-impact sports.